Solvent‐free synthesis of rotaxanes. Issue 2 (24th January 2019) - Inthasot, Alex; Tai, Tzu‐Yi; Chiu, Sheng‐Hsien
Abstract : Rotaxane‐type (macro)molecules are important materials in various fields of research, with many approaches for their synthesis having been developed over the past 30 years or so. When prepared in solution, the efficiency of interlocking pseudorotaxane complexes into the corresponding rotaxanes relies, to a great extent, on the affinity between the host and guest components; these interactions are not always sufficiently strong to overcome the deleterious effects of high reaction temperatures, competitive solvents, and low concentrations. Upon evaporating the solvent, however, the concentrations of the host and guest species increase significantly and, ultimately, their corresponding pseudorotaxanes can be generated with high efficiency in the solvent‐free residue. Furthermore, in the absence of the solvent, the influence of any disrupting byproducts (generated during the interlocking process) on the complexation equilibrium can also be largely reduced. Therefore, high synthetic efficiency and low consumption of solvents and energy can be expected when synthesizing rotaxanes under solvent‐free conditions. This mini‐review covers the main publications dealing with the solvent‐free syntheses of rotaxanes – those in which the interlocking step involves no solvent (or only a trace of it). Abstract : Compared to their in‐solution counterparts, the synthesis of rotaxanes under solvent‐free conditions can be more green and efficient. This mini‐review covers the main publications dealing with the solvent‐free syntheses of rotaxanes – those in which the interlocking step involves no solvent or only a trace of it.